2018
DOI: 10.1101/385823
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How much fear is in anxiety?

Abstract: The selective breeding for extreme behavior on the elevated plus-maze (EPM) resulted 8 in two mouse lines namely high-anxiety behaving (HAB) and low-anxiety behaving (LAB) mice. 9Using novel behavioral tests we demonstrate that HAB animals additionally exhibit maladaptive 10 escape behavior and defensive vocalizations, whereas LAB mice show profound deficits in escaping 11 from approaching threats which partially results from sensory deficits. We could relate these 12 behavioral distortions to tonic changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 126 publications
3
2
0
Order By: Relevance
“…We found that a dose of diazepam that was anxiolytic in wildtype mice had no effect in C3aR -/mice. Stretch attend postures, thought to reflect risk assessment behaviour 54 , are highly sensitive to pharmacological manipulation 50,80 and in agreement with our own findings, diazepam has been shown to specifically decrease SAPs in the absence of effects on open arm exploration 81 . Importantly, C3aR -/mice consistently performed more SAPs than other genotypes, and therefore floor effects cannot account for the pattern of results observed.…”
Section: Discussionsupporting
confidence: 87%
“…We found that a dose of diazepam that was anxiolytic in wildtype mice had no effect in C3aR -/mice. Stretch attend postures, thought to reflect risk assessment behaviour 54 , are highly sensitive to pharmacological manipulation 50,80 and in agreement with our own findings, diazepam has been shown to specifically decrease SAPs in the absence of effects on open arm exploration 81 . Importantly, C3aR -/mice consistently performed more SAPs than other genotypes, and therefore floor effects cannot account for the pattern of results observed.…”
Section: Discussionsupporting
confidence: 87%
“…We found that a dose of diazepam that was anxiolytic in wildtype mice had no effect in C3aR -/mice. Stretch attend postures, thought to reflect risk assessment behaviour 54 , are highly sensitive to pharmacological manipulation 50,80 and in agreement with our own findings, diazepam has been shown to specifically decrease SAPs in the absence of effects on open arm exploration 81 . Importantly, C3aR -/mice consistently performed more SAPs than other genotypes, and therefore floor effects cannot account for the pattern of results observed.…”
Section: Discussionsupporting
confidence: 87%
“…, are highly sensitive to pharmacological manipulation40,72 and in agreement with our own findings, diazepam has been shown to specifically decrease SAPs in the absence of effects on open arm exploration73 . Importantly, C3aR -/mice consistently performed more SAPs than other genotypes, and therefore floor effects cannot account for the pattern of results observed.…”
supporting
confidence: 89%
“…36 Many studies based their conclusions on these lines, yet recent work revealed that the mice considered as exhibiting low anxiety actually suffer from full retinal blindness, which could explain their seemingly fearless demeanor in the maze. 37 We have recently demonstrated a computational approach to measuring personality, starting from groups of mice. 38 Personality is defined as being consistent and stable across time and contexts while varying among individuals.…”
Section: Introductionmentioning
confidence: 99%
“… 36 Many studies based their conclusions on these lines, yet recent work revealed that the mice considered as exhibiting low anxiety actually suffer from full retinal blindness, which could explain their seemingly fearless demeanor in the maze. 37 …”
Section: Introductionmentioning
confidence: 99%